KF/Clinoptilolite Nanoparticles as a Heterogeneous Catalyst for Green Synthesis of pyrido[2,1-a]isoquinolines using Four-Component Reaction of Alkyl Bromides - Hamedani, Naghmeh F.; Ghazvini, Maryam; Sheikholeslami-Farahani, Fatemeh; Jamnani, Mohammad T.B. (Combinatorial Chemistry & High Throughput Screening, 2019)
Objective: KF/Clinoptilolite nanoparticles are employed as a heterogeneous catalyst for the preparation of pyrido[2,1-a]isoquinoline derivatives through a four-component reaction of isoquinoline, two different alkyl bromides and an electron deficient internal alkynes at ambient temperature in water as green solvent. Methods: In this research, (2,2-Diphenyl-1-picrylhydrazyl) radical trapping and reducing potential of ferric ion experiments was used for determining antioxidant activity of some newly synthesized compounds such as 5a, 5c, 5f and 5g and comparing results with synthetic antioxidants (TBHQ and BHT). Results: Compounds 5a, 5c, 5f and 5g display trace DPPH radical trapping and excellent reducing power of ferric ion. Furthermore, the power of some prepared compounds against Gram-positive and Gram-negative bacteria was proved by employing the disk dispersion experiment. Conclusion: The obtained results of disk diffusion test showed that compounds 5a, 5d and 5e prevented the bacterial growth. The reported procedure shows the advantages of clean reaction, high yield and simple purification.
Keywords: DPPH radical trapping